Types of Tropical Legume Leaf Meal in Dietary Concentrate Increased the Production of Forage-finished Beef Bali Cattle - Aoetpah, Aholiab; Oematan, Jacobus; Manfe, Manix; Sun, Wenbo; Banunaek, Musa; Wirawan, I Gusti Komang (Jurnal Ilmu-Ilmu Peternakan, 2024)
The objective of this experiment was to assess the production responses of forage-finished beef Bali cattle fed concentrated feed containing different types of leaf meal tropical legumes. Sixteen forage-finished male beef Bali cattle (Bos javanicus) with an average body weight of 175.20±27.85 kg and aged 1.5-2.5 years were raised for 54 days for data collection. A randomized completely block design was used, which consisted of four dietary treatments and four replicates. The dietary treatments, which were formulated to be isonitrogenous to provide 120 g/kg dry matter (DM) crude protein, included Cipelang grass (Pennisetum purpureum cv. Taiwan) as a basal diet (Con) or a control supplemented with a dietary concentrate containing either leaf meal of Gliricidia (Gliricidia sepium) 54.57% (Gliri), Leucaena (Leucaena leucocephala) 55.59% (Leu) or Moringa (Moringa oleifera) 40.85% (Mor). The feed intake, average daily gain (ADG), feed conversion ratio (FCR), digestibility and blood parameters were measured. The results showed that legume leaf meal supplementation significantly increased (P<0.05) feed intake, ADG, digestibility, haemoglobin and total leucocytes, while FCR was not affected (P>0.05). The highest ADG was recorded for Leu and Mor cattle, which was in line with the highest feed intake. In conclusion, forage-finished beef Bali cattle fed Cipelang grass as a basal diet grew faster when supplemented with dietary concentrate containing Moringa or Leucaena leaf meal.